Low-odor hot melt adhesive and preparation method thereof
Through the use of modified citrate and expanded graphite, the problems of poor antibacterial performance and insufficient heat resistance of hot melt adhesive in humid environments are solved, the heat resistance and flame retardant properties of hot melt adhesive are improved, and toughness is enhanced It also has low temperature cracking resistance, reduces odor concentration and extends service life.
Patent Information
- Application Number
- CN202411686356.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hot melt adhesives have poor antibacterial properties in humid environments, and insufficient heat resistance and flame retardant properties, resulting in bacterial corrosion and cracks adhesion on the surface of the material and reducing adhesion.
The preparation method of low-odor hot melt adhesive is adopted to form modified citrate esters through raw materials such as nanosilica and dodecyldimethylbenzyl ammonium chloride, which enhances cross-linking density and antibacterial properties, and uses expanded graphite to adsorption. Gas, reduces odor and improves heat resistance.
It improves the heat resistance, antibacterial properties and flame retardant properties of hot melt adhesives, enhances toughness and cracking resistance in low-temperature environments, reduces the odor concentration during heating, and extends the service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hot melt adhesives, in particular to a low-odor hot melt adhesive and a preparation method thereof. Background Art
[0002] Reactive polyurethane hot melt adhesive is an environmentally friendly hot melt adhesive. It not only has the convenient operation process characteristics of ordinary hot melt adhesive, but also contains active isocyanate groups, which can still undergo curing and cross-linking reactions with moisture in the air at room temperature, thereby obtaining excellent bonding properties, good flexibility and weather resistance, etc., and is therefore widely used in various industries such as consumer electronics, woodworking, home appliances, and textiles. Hot melt adhesive is solid at room temperature. When used, it is heated and melted and coated on the surface of the material, reacting with moisture in the air or attached to the surface of the material to generate a highly viscous polymer. Therefore, it has the characteristics of high initial viscosity and fast positioning speed of hot melt adhesive, as well as the characteristics of good water resistance and chemical resistance of reactive adhesives.
[0003] Hot melt adhesive has poor antibacterial properties in a humid environment, causing bacteria attached to the surface of the hot melt adhesive to corrode the surface of the material. In addition, current hot melt adhesives have poor heat resistance and flame retardancy. In high and low temperature environments, hot melt adhesives will crack, reducing the strength and adhesion of the hot melt adhesive. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a low-odor hot melt adhesive and a preparation method thereof, which solves the above-mentioned problems.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: A low-odor hot melt adhesive, composed of the following raw materials in parts by weight: 15-25 parts of polyamide resin, 8-10 parts of paraffin wax, 35-45 parts of pentaerythritol ester, 10-12 parts of modified citrate, 10-12 parts of flame-retardant polyol, 3-5 parts of ethylenediamine, 0.1-0.5 parts of tetrabutyl titanate, and 0.1-0.5 parts of tetrabutyl zirconate; The modified citrate comprises the following raw materials in parts by weight: acetyl tributyl citrate, dodecyl dimethyl benzyl ammonium chloride, nano silicon dioxide, acetone, and epichlorohydrin; The preparation method of modified citrate comprises the following steps: Step A1, adding nano-silicon dioxide into a three-necked flask filled with acetone; turning on a magnetic stirrer at a stirring speed of 300-600 rpm, and placing the three-necked flask in an ultrasonic cleaner for ultrasonic treatment, so that the nano-silicon dioxide forms a uniform and stable suspension in the acetone; the addition of nano-silicon dioxide increases the crosslinking density of the hot melt adhesive and improves the heat resistance.
[0006] Step A2, slowly adding epichlorohydrin to the nano-silica suspension after stirring and ultrasonication; after the epichlorohydrin is added, the temperature of the reaction system is increased to 50-70° C., and the stirring speed is kept unchanged, and the reaction time is 3-6 hours; the hydroxyl groups on the surface of the nano-silica react with the epoxy groups of the epichlorohydrin to form a chemical connection; Step A3, after the reaction is completed, dissolving dodecyl dimethyl benzyl ammonium chloride in acetone, preparing a solution and slowly adding it to the above reaction system; the amino group in dodecyl dimethyl benzyl ammonium chloride reacts with the active sites such as chlorine atoms connected to the nano-silica by epichlorohydrin, and the quaternary ammonium salt is grafted onto the nano-silica; dodecyl dimethyl benzyl ammonium chloride attracts the negative charge on the surface of the bacterial cell membrane through the quaternary ammonium salt group, and then inserts into the cell membrane, destroying the structure and function of the cell membrane, causing the leakage of intracellular substances, and finally killing the bacteria.
[0007] Step A4: After the reaction is completed, the reaction mixture is transferred to a centrifuge tube and centrifuged using a high-speed centrifuge; the supernatant is discarded and the precipitate is washed with acetone for 2-3 times, and centrifugation is performed after each washing. This step is to remove unreacted raw materials and by-products; the washed product is transferred to a vacuum drying oven and vacuum dried at 50-70°C for 6-12 hours to obtain a composite material; Step A5, mixing the composite material prepared above with tributyl acetyl citrate; using a ball mill to mix, the stirring speed is set to 200-500 rpm, the stirring time is 30-60 minutes, so that the two are fully mixed and uniform, and the final modified citrate is obtained. Citrate is a green and environmentally friendly plasticizer that can maintain toughness in a low temperature environment and prevent cracking of the adhesive layer.
[0008] Preferably, in step A1, the nano-silicon dioxide accounts for 5%-20% of the mass of the total reaction system; the ultrasonic power is set to 100-250W, and the ultrasonic time is 30-60 minutes.
[0009] Preferably, in step A2, epichlorohydrin is added at a rate of 0.5-1 mL per minute, and the amount used is 1-3 times the mass of the nano-silicon dioxide.
[0010] Preferably, the amount of dodecyldimethylbenzyl ammonium chloride used in step A3 is 0.5-1.5 times the mass of nano-silicon dioxide, and the reaction is stirred at 50-70° C. for 4-8 hours.
[0011] Preferably, in step A4, the centrifugal speed is set to 8000-12000 rpm, and the centrifugal time is 10-20 minutes, so that the solid product is precipitated at the bottom of the centrifuge tube.
[0012] Preferably, the mixing ratio of acetyl tributyl citrate in step A5 accounts for 30%-70% of the total mixture mass.
[0013] Preferably, the method for preparing the flame retardant polyol comprises the following steps: Step B1, dissolving a certain amount of 4-methyl-4-pentenoic acid in ethanol, then slowly adding an appropriate amount of sodium hydroxide solution, stirring and reacting at a temperature of 50° C. to 80° C. for 6 to 8 hours, monitoring the reaction progress by acid-base titration and the like, observing that 4-methyl-4-pentenoic acid is fully reacted, and obtaining a sodium 4-methyl-4-pentenoate solution; Step B2, adding p-aminobenzyl alcohol to the above-mentioned sodium 4-methyl-4-pentenoate solution, and adding dicyclohexylcarbodiimide, stirring and mixing evenly, heating to 85° C., and reacting under nitrogen for 0.5-1.5 h, and monitoring the reaction progress by thin layer chromatography, high performance liquid chromatography and the like; Step B3, heating the expanded graphite under vacuum conditions to remove adsorbed impurities and moisture. Then the pretreated expanded graphite is added to the above reaction system, and stirring is continued for 8-10 hours. The expanded graphite fully adsorbs and disperses the reaction products to obtain a flame retardant polyol. The expanded graphite can adsorb part of the gas during the heating process to achieve the ability to actively reduce odor. At the same time, the heat and cold resistance and corrosion resistance of the expanded graphite increase the service life of the hot melt adhesive.
[0014] Preferably, the usage ratio of the 4-methyl-4-pentenoic acid, sodium hydroxide, p-aminobenzyl alcohol and dicyclohexylcarbodiimide is: 0.1-0.3 mol: 400 mL: 0.2-0.3 mol: 1-1.2 mol.
[0015] A method for preparing a low-odor hot melt adhesive comprises the following steps: Step S1, adding polyamide resin, pentaerythritol ester, ethylenediamine, and tetrabutyl zirconate into a container, controlling the heating temperature to 110-130° C., stirring evenly, and dehydrating under vacuum conditions for 2-3 hours to obtain a premix; Step S2, slowly adding paraffin wax to the premix, adjusting the stirring speed so that the paraffin wax is evenly dispersed in the polyamide resin; Step S3, cooling the premix to 60-70° C., adding modified citrate, flame retardant polyol and tetrabutyl titanate under nitrogen conditions, and stirring at 80-130° C. under nitrogen conditions for 1-3 hours to obtain a low-odor hot melt adhesive.
[0016] The present invention has the following beneficial effects: Nano-silicon dioxide is added to a three-necked flask filled with acetone and stirred to form a uniform and stable suspension of the nano-silicon dioxide in the acetone; the addition of the nano-silicon dioxide increases the cross-linking density of the hot melt adhesive and improves the heat resistance; and epichlorohydrin is slowly added to the suspension, and the hydroxyl groups on the surface of the nano-silicon dioxide react with the epoxy groups of the epichlorohydrin to form a chemical connection; then dodecyldimethylbenzylammonium chloride is dissolved in acetone, and the amino groups in the dodecyldimethylbenzylammonium chloride react with the active sites such as chlorine atoms connected to the nano-silicon dioxide by epichlorohydrin, so that the quaternary ammonium salt is grafted onto the nano-silicon dioxide; the dodecyldimethylbenzylammonium chloride attracts the negative charge on the surface of the bacterial cell membrane through the quaternary ammonium salt group, and then inserts into the cell membrane, destroys the structure and function of the cell membrane, causes the leakage of intracellular substances, and finally kills the bacteria.
[0017] Citrate ester is a green and environmentally friendly plasticizer that releases a small amount of gas during heating and can maintain toughness in low temperature environments to prevent the adhesive layer from cracking. By adding modified citrate ester, the hot melt adhesive has both good toughness and antibacterial ability.
[0018] The hot melt adhesive is made of polyamide resin and pentaerythritol ester raw materials, which emits little odor when heated; and the expanded graphite can absorb part of the gas during the heating process to achieve the ability to actively reduce the odor. At the same time, the expanded graphite is resistant to heat and cold and corrosion, which increases the service life of the hot melt adhesive. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1 The invention provides a technical solution: the modified citric acid ester comprises the following raw materials in parts by weight: 11 parts of acetyl tributyl citrate, 9 parts of dodecyl dimethyl benzyl ammonium chloride, 3 parts of nano silicon dioxide, 12 parts of acetone and 11 parts of epichlorohydrin.
[0021] The preparation method of modified citrate ester consists of the following steps: Step A1, adding nano-silicon dioxide to a three-necked flask filled with acetone; turning on a magnetic stirrer with a stirring speed of 600 rpm, and placing the three-necked flask in an ultrasonic cleaner for ultrasonic treatment, so that the nano-silicon dioxide forms a uniform and stable suspension in acetone; the addition of nano-silicon dioxide increases the crosslinking density of the hot melt adhesive and improves the heat resistance, and the nano-silicon dioxide accounts for 20% of the total reaction system mass; the ultrasonic power is set to 250 W, and the ultrasonic time is 60 minutes.
[0022] Step A2, slowly adding epichlorohydrin to the nano-silica suspension after stirring and ultrasonication; after the epichlorohydrin is added, the temperature of the reaction system is increased to 70°C, and the stirring speed is kept unchanged, and the reaction time is 6 hours; the hydroxyl groups on the surface of the nano-silica react with the epoxy groups of the epichlorohydrin to form a chemical connection; the epichlorohydrin is added at a rate of 1 mL per minute, and the amount used is 3 times the mass of the nano-silica.
[0023] Step A3, after the reaction is completed, dissolving dodecyl dimethyl benzyl ammonium chloride in acetone, preparing a solution and then slowly adding it to the above reaction system; the amount of dodecyl dimethyl benzyl ammonium chloride used is 1.5 times the mass of nano-silicon dioxide, and the reaction is continuously stirred at 70° C. for 8 hours; the amino group in dodecyl dimethyl benzyl ammonium chloride reacts with active sites such as chlorine atoms connected to the nano-silicon dioxide by epichlorohydrin, and the quaternary ammonium salt is grafted onto the nano-silicon dioxide; dodecyl dimethyl benzyl ammonium chloride attracts the negative charge on the surface of the bacterial cell membrane through the quaternary ammonium salt group, and then inserts into the cell membrane, destroying the structure and function of the cell membrane, causing leakage of intracellular substances, and finally killing the bacteria.
[0024] Step A4: After the reaction is completed, the reaction mixture is transferred to a centrifuge tube and centrifuged using a high-speed centrifuge; the supernatant is discarded and the precipitate is washed with acetone for 3 times, and centrifugation is performed after each washing; the centrifugal speed is set to 12000rpm and the centrifugal time is 20 minutes, so that the solid product is precipitated at the bottom of the centrifuge tube. This step is to remove unreacted raw materials and by-products; the washed product is transferred to a vacuum drying oven and vacuum dried at 70°C for 12 hours to obtain a composite material; Step A5, mixing the composite material prepared above with tributyl acetyl citrate; the mixing ratio of tributyl acetyl citrate accounts for 70% of the total mixture mass; using a ball mill for mixing, the stirring speed is set to 500 rpm, the stirring time is 60 minutes, so that the two are fully mixed and uniform, and the final modified citrate is obtained. Citrate is a green and environmentally friendly plasticizer that can maintain toughness in a low temperature environment and prevent cracking of the adhesive layer.
[0025] Example 2 The present invention provides a technical solution: The modified citrate ester has the following raw materials in parts by weight: 10 parts of acetyl tributyl citrate, 8 parts of dodecyl dimethyl benzyl ammonium chloride, 2 parts of nano silicon dioxide, 10 parts of acetone, and 10 parts of epichlorohydrin.
[0026] The preparation method of modified citrate ester consists of the following steps: Step A1, adding nano-silicon dioxide to a three-necked flask filled with acetone; turning on a magnetic stirrer with a stirring speed of 300 rpm, and placing the three-necked flask in an ultrasonic cleaner for ultrasonic treatment, so that the nano-silicon dioxide forms a uniform and stable suspension in acetone; the addition of nano-silicon dioxide increases the crosslinking density of the hot melt adhesive and improves the heat resistance, and the nano-silicon dioxide accounts for 5% of the total reaction system mass; the ultrasonic power is set to 100 W, and the ultrasonic time is 30 minutes.
[0027] Step A2, slowly adding epichlorohydrin to the nano-silica suspension after stirring and ultrasonication; after the epichlorohydrin is added, the temperature of the reaction system is increased to 50°C, and the stirring speed is kept unchanged, and the reaction time is 3 hours; the hydroxyl groups on the surface of the nano-silica react with the epoxy groups of the epichlorohydrin to form a chemical connection; the epichlorohydrin is added at a rate of 0.5 mL per minute, and the amount used is 1 times the mass of the nano-silica.
[0028] Step A3, after the reaction is completed, dissolving dodecyl dimethyl benzyl ammonium chloride in acetone, preparing a solution and then slowly adding it to the above reaction system; the amount of dodecyl dimethyl benzyl ammonium chloride used is 0.5 times the mass of nano-silicon dioxide, and the reaction is continuously stirred at 50° C. for 4 hours; the amino group in dodecyl dimethyl benzyl ammonium chloride reacts with active sites such as chlorine atoms connected to the nano-silicon dioxide by epichlorohydrin, and the quaternary ammonium salt is grafted onto the nano-silicon dioxide; dodecyl dimethyl benzyl ammonium chloride attracts the negative charge on the surface of the bacterial cell membrane through the quaternary ammonium salt group, and then inserts into the cell membrane, destroying the structure and function of the cell membrane, causing leakage of intracellular substances, and finally killing the bacteria.
[0029] Step A4: After the reaction is completed, the reaction mixture is transferred to a centrifuge tube and centrifuged using a high-speed centrifuge; the supernatant is discarded and the precipitate is washed with acetone for 2 times, and centrifugation is performed after each washing; the centrifugal speed can be set to 8000 rpm and the centrifugal time is 10 minutes, so that the solid product is precipitated at the bottom of the centrifuge tube. This step is to remove unreacted raw materials and by-products; the washed product is transferred to a vacuum drying oven and vacuum dried at 50°C for 6 hours to obtain a composite material; Step A5, mixing the composite material prepared above with tributyl acetyl citrate; the mixing ratio of tributyl acetyl citrate accounts for 30% of the total mixture mass; using a ball mill for mixing, the stirring speed is set to 200 rpm, the stirring time is 30 minutes, so that the two are fully mixed and uniform, and the final modified citrate is obtained. Citrate is a green and environmentally friendly plasticizer that can maintain toughness in a low temperature environment and prevent the adhesive layer from cracking.
[0030] Example 3 The present invention provides a technical solution: The modified citrate comprises the following raw materials in parts by weight: 12 parts of acetyl tributyl citrate, 10 parts of dodecyl dimethyl benzyl ammonium chloride, 4 parts of nano silicon dioxide, 14 parts of acetone, and 12 parts of epichlorohydrin.
[0031] The preparation method of modified citrate ester consists of the following steps: Step A1, adding nano-silicon dioxide to a three-necked flask filled with acetone; turning on a magnetic stirrer with a stirring speed of 600 rpm, and placing the three-necked flask in an ultrasonic cleaner for ultrasonic treatment, so that the nano-silicon dioxide forms a uniform and stable suspension in acetone; the addition of nano-silicon dioxide increases the crosslinking density of the hot melt adhesive and improves the heat resistance, and the nano-silicon dioxide accounts for 20% of the total reaction system mass; the ultrasonic power is set to 250 W, and the ultrasonic time is 60 minutes.
[0032] Step A2, slowly adding epichlorohydrin to the nano-silica suspension after stirring and ultrasonication; after the epichlorohydrin is added, the temperature of the reaction system is increased to 70°C, and the stirring speed is kept unchanged, and the reaction time is 6 hours; the hydroxyl groups on the surface of the nano-silica react with the epoxy groups of the epichlorohydrin to form a chemical connection; the epichlorohydrin is added at a rate of 1 mL per minute, and the amount used is 3 times the mass of the nano-silica.
[0033] Step A3, after the reaction is completed, dissolving dodecyl dimethyl benzyl ammonium chloride in acetone, preparing a solution and then slowly adding it to the above reaction system; the amount of dodecyl dimethyl benzyl ammonium chloride used is 1.5 times the mass of nano-silicon dioxide, and the reaction is continuously stirred at 70° C. for 8 hours; the amino group in dodecyl dimethyl benzyl ammonium chloride reacts with active sites such as chlorine atoms connected to the nano-silicon dioxide by epichlorohydrin, and the quaternary ammonium salt is grafted onto the nano-silicon dioxide; dodecyl dimethyl benzyl ammonium chloride attracts the negative charge on the surface of the bacterial cell membrane through the quaternary ammonium salt group, and then inserts into the cell membrane, destroying the structure and function of the cell membrane, causing leakage of intracellular substances, and finally killing the bacteria.
[0034] Step A4: After the reaction is completed, the reaction mixture is transferred to a centrifuge tube and centrifuged using a high-speed centrifuge; the supernatant is discarded and the precipitate is washed with acetone for 3 times, and centrifugation is performed after each washing; the centrifugal speed is set to 12000rpm and the centrifugal time is 20 minutes, so that the solid product is precipitated at the bottom of the centrifuge tube. This step is to remove unreacted raw materials and by-products; the washed product is transferred to a vacuum drying oven and vacuum dried at 70°C for 12 hours to obtain a composite material; Step A5, mixing the composite material prepared above with tributyl acetyl citrate; the mixing ratio of tributyl acetyl citrate accounts for 70% of the total mixture mass; using a ball mill for mixing, the stirring speed is set to 500 rpm, the stirring time is 60 minutes, so that the two are fully mixed and uniform, and the final modified citrate is obtained. Citrate is a green and environmentally friendly plasticizer that can maintain toughness in a low temperature environment and prevent cracking of the adhesive layer.
[0035] Example 4 The present invention provides a technical solution: The method for preparing the flame retardant polyol consists of the following steps: Step B1, dissolving a certain amount of 4-methyl-4-pentenoic acid in ethanol, then slowly adding an appropriate amount of sodium hydroxide solution, stirring and reacting at a temperature of 80° C. for 8 hours, monitoring the reaction progress by acid-base titration and the like, observing that 4-methyl-4-pentenoic acid is fully reacted, and obtaining a sodium 4-methyl-4-pentenoate solution; Step B2, adding p-aminobenzyl alcohol to the above-mentioned sodium 4-methyl-4-pentenoate solution, and adding dicyclohexylcarbodiimide, stirring and mixing evenly, heating to 85° C., and reacting under nitrogen for 1.5 hours, and monitoring the reaction progress by thin layer chromatography, high performance liquid chromatography and the like; Step B3, heat the expanded graphite under vacuum conditions to remove adsorbed impurities and moisture. Then add the pretreated expanded graphite to the above reaction system and continue stirring for 10 hours. The expanded graphite fully adsorbs and disperses the reaction products to obtain a flame retardant polyol. The expanded graphite can adsorb part of the gas during the heating process to achieve the ability to actively reduce odor. At the same time, the heat and cold resistance and corrosion resistance of the expanded graphite increase the service life of the hot melt adhesive. The amount ratio of 4-methyl-4-pentenoic acid, sodium hydroxide, p-aminobenzyl alcohol and dicyclohexylcarbodiimide is: 0.3mol: 400mL: 0.3mol: 1.2mol.
[0036] Example 5 The present invention provides a technical solution: The method for preparing the flame retardant polyol consists of the following steps: Step B1, dissolving a certain amount of 4-methyl-4-pentenoic acid in ethanol, then slowly adding an appropriate amount of sodium hydroxide solution, stirring and reacting at a temperature of 50° C. for 6 hours, monitoring the reaction progress by acid-base titration and the like, observing that 4-methyl-4-pentenoic acid is fully reacted, and obtaining a sodium 4-methyl-4-pentenoate solution; Step B2, adding p-aminobenzyl alcohol to the above-mentioned sodium 4-methyl-4-pentenoate solution, and adding dicyclohexylcarbodiimide, stirring and mixing evenly, heating to 85° C., and reacting under nitrogen for 0.5 h, and monitoring the reaction progress by thin layer chromatography, high performance liquid chromatography and the like; Step B3, heat the expanded graphite under vacuum conditions to remove adsorbed impurities and moisture. Then add the pretreated expanded graphite to the above reaction system and continue stirring for 8 hours. The expanded graphite fully adsorbs and disperses the reaction products to obtain flame retardant polyols. The expanded graphite can adsorb part of the gas during the heating process to achieve the ability to actively reduce odor. At the same time, the heat and cold resistance and corrosion resistance of the expanded graphite increase the service life of the hot melt adhesive. The dosage ratio of 4-methyl-4-pentenoic acid, sodium hydroxide, p-aminobenzyl alcohol and dicyclohexylcarbodiimide is: 0.1mol: 400mL: 0.2mol: 1mol.
[0037] Example 6 According to Examples 1 and 4, the present invention provides a technical solution: a low-odor hot melt adhesive, composed of the following raw materials in parts by weight, 15 parts of polyamide resin, 8 parts of paraffin, 35 parts of pentaerythritol ester, 10 parts of modified citrate, 10 parts of flame retardant polyol, 3 parts of ethylenediamine, 0.1 parts of tetrabutyl titanate, and 0.1 parts of tetrabutyl zirconate, wherein ethylenediamine is a chain extender, tetrabutyl titanate is a coupling agent, and tetrabutyl zirconate is a catalyst.
[0038] A method for preparing a low-odor hot melt adhesive comprises the following steps: Step S1, adding polyamide resin, pentaerythritol ester, ethylenediamine, and tetrabutyl zirconate into a container, controlling the heating temperature at 130° C. to stir evenly, and dehydrating under vacuum conditions for 3 hours to obtain a premix; Step S2, slowly adding paraffin wax to the premix, adjusting the stirring speed so that the paraffin wax is evenly dispersed in the polyamide resin; Step S3, cooling the premix to 70° C., adding modified citrate, flame retardant polyol and tetrabutyl titanate under nitrogen conditions, and stirring at 130° C. under nitrogen conditions for 3 hours to obtain a low-odor hot melt adhesive.
[0039] Example 7 According to Examples 2 and 4, the present invention provides a technical solution: a low-odor hot melt adhesive, composed of the following raw materials in parts by weight, 25 parts of polyamide resin, 10 parts of paraffin, 45 parts of pentaerythritol ester, 12 parts of modified citrate, 12 parts of flame retardant polyol, 5 parts of ethylenediamine, 0.5 parts of tetrabutyl titanate, and 0.5 parts of tetrabutyl zirconate, wherein ethylenediamine is a chain extender, tetrabutyl titanate is a coupling agent, and tetrabutyl zirconate is a catalyst.
[0040] A method for preparing a low-odor hot melt adhesive comprises the following steps: Step S1, adding polyamide resin, pentaerythritol ester, ethylenediamine, and tetrabutyl zirconate into a container, controlling the heating temperature at 110° C. to stir evenly, and dehydrating under vacuum conditions for 2 hours to obtain a premix; Step S2, slowly adding paraffin wax to the premix, adjusting the stirring speed so that the paraffin wax is evenly dispersed in the polyamide resin; Step S3, cooling the premix to 60° C., adding modified citrate, flame retardant polyol and tetrabutyl titanate under nitrogen conditions, and stirring at 80° C. under nitrogen conditions for 1 hour to obtain a low-odor hot melt adhesive.
[0041] Example 8 According to Examples 3 and 4, the present invention provides a technical solution: a low-odor hot melt adhesive, composed of the following raw materials in parts by weight, 20 parts of polyamide resin, 9 parts of paraffin, 40 parts of pentaerythritol ester, 11 parts of modified citrate, 11 parts of flame retardant polyol, 4 parts of ethylenediamine, 0.3 parts of tetrabutyl titanate, and 0.3 parts of tetrabutyl zirconate.
[0042] A method for preparing a low-odor hot melt adhesive comprises the following steps: Step S1, adding polyamide resin, pentaerythritol ester, ethylenediamine, and tetrabutyl zirconate into a container, controlling the heating temperature at 130° C. to stir evenly, and dehydrating under vacuum conditions for 3 hours to obtain a premix; Step S2, slowly adding paraffin wax to the premix, adjusting the stirring speed so that the paraffin wax is evenly dispersed in the polyamide resin; Step S3, cooling the premix to 70° C., adding modified citrate, flame retardant polyol and tetrabutyl titanate under nitrogen conditions, and stirring at 130° C. under nitrogen conditions for 3 hours to obtain a low-odor hot melt adhesive.
[0043] Comparative Example 1 This comparative example is a low-odor hot melt adhesive, which differs from Example 6 in that no modified citrate is added, and the rest is the same.
[0044] Comparative Example 2 This comparative example is a low-odor hot melt adhesive, which differs from Example 6 in that no flame retardant polyol is added, and the rest is the same.
[0045] The hot melt adhesives prepared in Examples 6-8 and Comparative Examples 1-2 were subjected to performance tests, and the test results are shown in Table 1: Table 1 Performance test results of the hot melt adhesives prepared in Examples 6-8 and Comparative Examples 1-2
[0046] As can be seen from Table 1, the low-odor hot melt adhesive of the present invention has increased the excellent antibacterial durability of modified citrate ester, has outstanding antibacterial effect, has good toughness, and has outstanding anti-cracking ability under low temperature environment; the addition of flame retardant polyol has a higher heat resistance temperature, improves the flame retardant performance of the hot melt adhesive, and at the same time, the concentration of volatiles is low during the heating process, reducing the volatile odor.
[0047] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions. The sentence "including an element defined by ... does not exclude the existence of other identical elements in the process, method, article or device including the element".
[0048] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low odor hot melt adhesive, characterized in that: The invention is composed of the following raw materials in parts by weight: 15-25 parts of polyamide resin, 8-10 parts of paraffin wax, 35-45 parts of pentaerythritol ester, 10-12 parts of modified citrate, 10-12 parts of flame retardant polyol, 3-5 parts of ethylenediamine, 0.1-0.5 parts of tetrabutyl titanate, and 0.1-0.5 parts of tetrabutyl zirconate; The modified citrate comprises the following raw materials in parts by weight: 10-12 parts of acetyl tributyl citrate, 8-10 parts of dodecyl dimethyl benzyl ammonium chloride, 2-4 parts of nano silicon dioxide, 10-14 parts of acetone, and 10-12 parts of epichlorohydrin; The preparation method of modified citrate comprises the following steps: Step A1, adding nano-silicon dioxide into a three-necked flask filled with acetone, turning on a magnetic stirrer at a stirring speed of 300-600 rpm, and placing the three-necked flask in an ultrasonic cleaner for ultrasonic treatment, so that the nano-silicon dioxide forms a uniform and stable suspension in the acetone; Step A2, slowly adding epichlorohydrin to the nano-silicon dioxide suspension after stirring and ultrasonication; after the epichlorohydrin is added, the temperature of the reaction system is increased to 50-70° C., and the stirring speed is kept unchanged, and the reaction time is 3-6 hours; Step A3: After the reaction is completed, dissolve dodecyldimethylbenzyl ammonium chloride in acetone to prepare a solution, and then slowly add it into the reaction system after the reaction in step A2 is completed; Step A4, after the reaction is completed, the reaction mixture is transferred to a centrifuge tube, and centrifuged using a high-speed centrifuge; the supernatant is poured out, and the precipitate is washed with acetone for 2-3 times, and centrifugation is performed after each washing. The washed product is transferred to a vacuum drying oven, and vacuum dried at 50-70° C. for 6-12 hours to obtain a composite material; Step A5, mixing the composite material prepared in step A4 with acetyl tributyl citrate; using a ball mill to mix, setting the stirring speed to 200-500 rpm, and stirring time to 30-60 minutes, so that the two are fully mixed and uniform, to obtain the final modified citrate.
2. The low-odor hot melt adhesive according to claim 1, characterized in that: In the step A1, the nano-silicon dioxide accounts for 5%-20% of the total reaction system mass; the ultrasonic power is set to 100-250W, and the ultrasonic time is 30-60 minutes.
3. The low-odor hot melt adhesive according to claim 1, characterized in that: In the step A2, epichlorohydrin is added at a rate of 0.5-1 mL per minute, and the amount used is 1-3 times the mass of the nano-silicon dioxide.
4. The low-odor hot melt adhesive according to claim 1, characterized in that: In step A3, the amount of dodecyldimethylbenzylammonium chloride used is 0.5-1.5 times the mass of nano-silicon dioxide, and the reaction is stirred at 50-70° C. for 4-8 hours.
5. The low-odor hot melt adhesive according to claim 1, characterized in that: In step A4, the centrifugal speed is set to 8000-12000 rpm, and the centrifugal time is 10-20 minutes, so that the solid product is precipitated at the bottom of the centrifuge tube.
6. The low-odor hot melt adhesive according to claim 1, characterized in that: In the step A5, the mixing ratio of acetyl tributyl citrate accounts for 30%-70% of the total mixture mass.
7. The low-odor hot melt adhesive according to claim 1, characterized in that: The method for preparing the flame retardant polyol comprises the following steps: Step B1, dissolving 4-methyl-4-pentenoic acid in ethanol, then slowly adding sodium hydroxide solution, stirring and reacting at a temperature of 50° C. to 80° C. for 6 to 8 hours, monitoring the reaction progress by acid-base titration method, and the 4-methyl-4-pentenoic acid is fully reacted to obtain a sodium 4-methyl-4-pentenoate solution; Step B2, adding p-aminobenzyl alcohol to the above sodium 4-methyl-4-pentenoate solution, and adding dicyclohexylcarbodiimide, stirring and mixing evenly, heating to 85° C., and reacting under nitrogen for 0.5-1.5 h; Step B3, heating the expanded graphite under vacuum conditions to remove adsorbed impurities and moisture; then adding the pretreated expanded graphite to the above reaction system, stirring continuously for 8-10 hours, so that the expanded graphite fully absorbs and disperses the reaction product to obtain a flame retardant polyol.
8. The low-odor hot melt adhesive according to claim 7, characterized in that: The usage ratio of the 4-methyl-4-pentenoic acid, sodium hydroxide, p-aminobenzyl alcohol and dicyclohexylcarbodiimide is: 0.1-0.3 mol: 400 mL: 0.2-0.3 mol: 1-1.2 mol.
9. A method for preparing a low-odor hot melt adhesive as claimed in claim 1, characterized in that: The following steps are involved: Step S1, adding polyamide resin, pentaerythritol ester, ethylenediamine, and tetrabutyl zirconate into a container, controlling the heating temperature to 110-130° C., stirring evenly, and dehydrating under vacuum conditions for 2-3 hours to obtain a premix; Step S2, slowly adding paraffin wax to the premix, adjusting the stirring speed so that the paraffin wax is evenly dispersed in the polyamide resin; Step S3, cooling the premix to 60-70° C., adding modified citrate, flame retardant polyol and tetrabutyl titanate under nitrogen conditions, and stirring at 80-130° C. under nitrogen conditions for 1-3 hours to obtain a low-odor hot melt adhesive.
Citation Information
Patent Citations
Formula of oil-resistant hot melt adhesive and production process of hot melt adhesive
CN102559128A
Preparation method of aerodynamic sealing luminous pressure-sensitive adhesive
CN110564357A
High-temperature-aging-resistant adhesive for magic tapes and manufacturing method thereof
CN113583621A
High-performance polyester hot melt adhesive and preparation method thereof
CN118703150A
Hot-melt adhesive
JP2004256642A
